A comparative analysis of the information duties in Belgian and American occupational pensions. Issue 1 (March 2020) - Denys, Marjolein; Pratt, David; Stevens, Yves
Both the United States of America and Belgium attach great importance to communication duties in occupational pensions. Several legal sources in both countries provide the right to be informed to participants. The legislation in both countries seeks to ensure accurate, correct, transparent and understandable communication. Despite this resemblance, there are some differences in communication. The countries can learn from one another. Based on a theoretical framework developed in and for the European Union, the communication rights and duties in the USA and Belgium are analysed. This analysis leads to a better understanding of the different legal responsibilities, transparency rules, simplification efforts and technical correctness of the types of occupational pension information analyzed.